Public goods, private goods - Geuss, Raymond (Princeton monographs in philosophy., 2001)
Much political thinking today, particularly that influenced by liberalism, assumes a clear distinction between the public and the private, and holds that the correct understanding of this should weigh heavily in our attitude to human goods. It is, for instance, widely held that the state may address human action in the ''public'' realm but not in the ''private.'' In Public Goods, Private Goods Raymond Geuss exposes the profound flaws of such thinking and calls for a more nuanced approach. Drawing on a series of colorful examples from the ancient world, he illustrates some of the many ways in w.